(untitled) (Fiep Bulletin - online, 2011)
The purpose of this bibliographical study was to identify the importance of therapeutic touch. Were performed to research databases and an active search in national journals, plus a selection of existing studies that addressed the theme ringtone, physiology of touch, especially the use of a therapeutic touch through massage. Realize that the ability to relate to other human beings is becoming more distant, leads him to discover the vital importance of non-verbal, the special relationship between the skin and touch to the physical and mental health. The language of the senses is able to expand the appreciation of others or the world, and deepen understanding about them. Discover the immune functions of the skin and the importance of touch, the effects of their deprivation will give a higher quality to work as massage therapist.